Plant bioactives in carrageenan biocomposites for food preservation and quality monitoring: Functional performance and safety considerations - Rubie Mavelil-Sam; Sabu Thomas; Hanna J. Maria; Andreas L. Lopata; Katia Alexander; Mohan V. Jacob (Carbohydrate Polymers, 2026)

PICOGRAM - informing coral reef resilience-based management through prediction of individual coral organismal growth, recruitment, and mortality - Imad Eddine Tibermacine; Ved Chirayath; Soufyane Bouchelaghem; Thomas Oliver; Courtney Couch; Michael Akridge; Sam Purkis (Frontiers in Marine Science, 2026)
Coral reef science and management are increasingly relying on imagery-based methods to expand monitoring capacity and improve the assessment of reef condition. However, scalable monitoring requires coral colony-scale segmentation from high-resolution underwater imagery and orthomosaic-derived survey products, while dense manual pixel-wise annotation remains costly, time-consuming, and inconsistent across sites and imaging conditions. Operational methods therefore need to generalize across sites, optics, and platforms while providing calibrated confidence with minimal quality-assurance effort. We introduce NASA/NOAA PICOGRAM, an open-source extension inspired by the NASA NeMO-Net ecosystem, as an image-only, user-promptable framework for automated coral colony detection, segmentation, and percent-cover estimation. The current study evaluates segmentation and cover estimation from underwater still images and orthomosaic-derived image tiles; repeated site imagery can subsequently support longitudinal analyses of colony change. PICOGRAM adapts a Segment Anything Model (SAM)-style encoder–decoder to underwater imagery while freezing the visual backbone and training only low-rank adapters, a lightweight prompt encoder for points and boxes, and a transformer mask decoder. PICOGRAM is supervised using Simple Linear Iterative Clustering (SLIC)-derived pseudolabels. Enhanced images are over-segmented into superpixels, scored with underwater-aware color, texture, and edge features, smoothed on a superpixel graph, and converted to masks using a Potts conditional random field (CRF). Mask-level non-maximum suppression and a two-round curriculum further tighten pseudo-label selection. A quality head predicts mask Intersection-overUnion (IoU) and is calibrated on validation data to support site-specific operating thresholds. Using NOAA National Coral Reef Monitoring Program benthic survey imagery, PICOGRAM is evaluated on a site-disjoint expert-labeled hold-out ( n = 137). The method attains an IoU of 87.5% in-domain and 82.5% cross-site, with strong boundary accuracy (bIoU 82.1%) and favorable precision–recall behavior (93.0% precision; PR–AUC 94.5%). Quality scores are well calibrated, with an expected calibration error of 0.028, and ambiguous masks can be refined efficiently with an average of 1.8 clicks to reach 0.90 IoU. Percent-cover estimates closely match expert annotations (Pearson r = 0.98, mean absolute error of 1.2 percentage points; bias −0.3 ± 2.1 pp). Across matched operating points, PICOGRAM modestly but consistently outperforms strong baselines based on SAM 1, SAM 2, YOLOv11, and CoralScop. By reducing the need for manual pixel-wise training masks and enabling calibrated, low-click refinement, PICOGRAM provides deployable coral colony-scale segmentation and cover estimation from NOAA underwater imagery and orthomosaic-derived tiles. This capability can support higher spatial coverage in coral monitoring programs, improve quality control in large image collections, and facilitate rapid post disturbance assessment, while future longitudinal validation will extend the framework toward direct estimation of colony growth, recruitment, and mortality.

FeCl3/KOH two steps activated biocarbon with hierarchical porosity and oxygen-rich for enhanced supercapacitor applications - Amadou Belal Gueye; Sam John; Martin George Thomas; Jephin K. Jose; Modou Fall; Manoj Balachandran; Sabu Thomas (Biomass and Bioenergy, 2026)

Heparin-incorporated whey protein isolate-derived hydrogels with an intended dual function as snakebite wound dressings and drug delivery systems inhibit spitting cobra venom-induced cytotoxicity - Matthew J. Gray; Daniel K. Baines; Gabrielle De Castro; Thomas Cobb; Layla A. Tyrrell; Sam J. Hyam; Alan M. Smith; Nicholas R. Casewell; Sarah L. Allinson; Timothy E.L. Douglas; Steven R. Hall (Toxicon, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Transcriptomic landscape of oral potentially malignant disorders: a meta-analysis approach - Vaishnav Vasudevan; Gangotri Siddappa; Reba Elsa Sam; H. K. Madhumathi; Anela Thomas; Sumsum P. Sunny; Vivek Shetty; Vidya Bhushan; Yogesh Dokhe; Vijay Pillai; Praveen Birur; Moni A. Kuriakose; et al. (Human Cell, 2026)

Population Genomics of a Cosmopolitan Weed Provides Insights Into Its Local Adaptation and Recent Demographic History - Marilia Souza Lucas; Christoph Rosche; Isabell Hensen; Stefan G. Michalski; Dávid U. Nagy; Diana Gamba; Renske E. Onstein; Karime Abidkulova; Mohammad Al‐Gharaibeh; Ali A. Al‐Namazi; Sirwan Babaei; Fernando Bastida; et al. (Molecular Ecology, 2026)
Invasive plant species present a growing ecological and economic challenge, and often adapt rapidly to their novel environments through complex demographic and evolutionary processes. Invasion genomics offers powerful tools to disentangle these processes, but most studies rely on geographically narrow sampling across native and non‐native ranges. Erigeron canadensis is a cosmopolitan weed native to North America that has successfully invaded diverse climates worldwide. We used double‐digest restriction site‐associated DNA sequencing (ddRADseq) to investigate the genetic diversity and structure of 280 E. canadensis populations across the Northern Hemisphere. We found that native and non‐native populations maintained comparable genetic diversity. Population structure analyses revealed four genetic clusters that were mainly differentiated along latitudinal and aridity gradients. However, one cluster was strongly overrepresented in the non‐native compared to the native range. In the native range, genetic differentiation was shaped by spatial and environmental gradients, while in non‐native regions human‐mediated dispersal and repeated introductions disrupted environmentally driven genetic structure. Migration network analyses revealed limited intercontinental connectivity and a possible role of long‐distance dispersal in within‐range expansions. Genomic offset analyses showed that genotype‐environment mismatches in non‐native populations associated with reduced growth and reproduction. Together, our results indicate that the invasion dynamics of E. canadensis were driven by multiple introductions, population admixture, and lineage sorting, while some genotypes contributed disproportionately to the spread of this invader. The presence of apparent maladaptation suggests that even long‐established invaders may still be evolving in response to their novel environment, raising concerns about potential future expansions.

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Lagged streamflow depletion due to pumping-induced stream drying: Incorporation into analytical streamflow depletion estimation methods - Sam Zipper; Ian Gambill; Monty Schmitt; Claire Kouba; Leland Scantlebury; Thomas Harter; Nicholas P. Murphy (Journal of Hydrology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Exploring the impact of local floral quality and land use on bumble bee communities: Insights into common and at-risk species - Jonathan Tetlie; Catherine Dana; Jared Thomas; Sam W. Heads; Alexandra Harmon-Threatt (Biological Conservation, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Comparing the impact of feedback on excess calories and physical activity calorie equivalent (PACE) information on consumer behaviour in an online hypothetical restaurant setting - Andrew Jones; Thomas Gough; Rebecca Evans; Amy Finlay; Jay J. Duckworth; Sam Burton; Abigail K. Rose; Eric Robinson (Appetite, 2026)

Spatial variation and habitat preference of reef fish and gastropod assemblages from two coastal habitats in subtropical reef, Port Shelter, Hong Kong - Sam King Fung Yiu; Thomas Ka Tung Leung; Gabriel Yeung Lee; Meng Yan (Marine Environmental Research, 2025)

West Nile virus in Culex mosquitoes and dead birds from the San Gabriel Valley, California, 2021–2022 - Christine A. Mariskanish; Tristan Hallum; Sam S. Lee; Christian K. Fung; Thomas R. Tchingambu; Matthew A. Conte; Jun Hang (Archives of Virology, 2025)

Cellular senescence—from solid organs to vascularized composite allotransplants - Leonard Knoedler; Andreas Schroeter; Jasper Iske; Jillian Dean; Sam Boroumand; Thomas Schaschinger; Tobias Niederegger; Samuel Knoedler; Adriana C. Panayi; Max Heiland; Stefan G. Tullius; Bohdan Pomahac; et al. (GeroScience, 2025)
Vascularized composite allotransplantation (VCA) has emerged as a novel therapy approach to restore form and function in patients with severe tissue defects of the face, hand, and abdominal wall, among other anatomical regions. The composite allografts comprise different tissues such as skin, muscle, or bone. Clinical data demonstrate promising mid- and long-term outcomes following VCA surgery, but our understanding of the cellular interactions and molecular pathways in VCA surgery is oftentimes deduced from solid organ transplantation (SOT). In SOT, the concept of cellular senescence has grown increasingly popular which is characterized by a permanent cellular proliferation arrest in response to endogenous and exogenous stimuli. Senescent cells, through the release of mitochondrial DNA and secretion of proinflammatory proteins, can amplify the immunogenicity of transplants, hindering graft acceptance and longevity. This understanding has paved the way for novel interventions, including the use of senolytics—agents that selectively eliminate senescent cells—to modulate immune responses and mediate immunotolerance. There is a body of evidence that underlines the therapeutic potential of senescence to improve SOT outcomes; however, the relevance of senescence to VCA outcomes remains elusive. In this review, we aim to summarize the current literature on senescence in different solid organ transplants and outline the potential impact of senescence on VCA outcomes. This knowledge may help providers develop a broader understanding of the cellular and molecular landscape in VCA to develop targeted therapies and advance VCA patient care.

Regional conservation genomics: insights and opportunities from northern Australia - Teigan Cremona; Brenton von Takach; Robyn Shaw; Alexander Carey; Bridget Campbell; Skye Cameron; Renee Catullo; Caroline Chong; Saul Cowen; Danielle Edwards; Emilie Ens; Tony Griffiths; et al. (Biodiversity and Conservation, 2025)
Biodiversity conservation in northern Australia is characterised by high endemism, data deficiency, and high Indigenous land tenure and population. The Northern Australia Conservation Genomics Forum brought together experts to explore current genetic research with particular emphasis on integration of genomics within conservation practices. We discuss the regional biodiversity of northern Australia, highlighting the unique biogeographic patterns, known and unknown species diversity, and ongoing threats such as habitat degradation, altered fire regimes, invasive species, and climate change. This article synthesises key themes from the forum, including the current application of genomics in conservation, gaps and areas of need and opportunity to advance species conservation in this sparsely populated, yet iconic region of Australia. We highlight the need to expand collaborative research partnerships across land tenures with Indigenous organisations, pastoralists, government and non-government organisations, which is crucial for the effective study and conservation of the region’s biodiversity. The paper identifies the challenges and opportunities in applying genomic data to conservation strategies and applied management, including species translocations and habitat management, while acknowledging the limitations and gaps in current research and collections. The insights from this forum emphasise the advantages in using genomics to inform conservation decisions, and the need for continued research and collaboration to protect northern Australia’s unique biodiversity.

Effects of climate on leaf phenolics, insect herbivory, and their relationship in pedunculate oak (Quercus robur) across its geographic range in Europe - Elena Valdés-Correcher; Yasmine Kadiri; Audrey Bourdin; Anna Mrazova; Flavius Bălăcenoiu; Manuela Branco; Michal Bogdziewicz; Mona Chor Bjørn; Thomas Damestoy; Jovan Dobrosavljević; Maria Faticov; Sofia Gripenberg; et al. (Oecologia, 2025)
An increase in biotic interactions towards lower latitudes is one of the most consistent patterns in ecology. Higher temperatures and more stable climatic conditions at low latitudes are thought to enhance biotic interactions, accelerating biological evolution and leading to stronger anti-herbivore defences in plants. However, some studies report contradictory findings, highlighting the need for further investigation into the underlying mechanisms. We used a combination of field observations and feeding trials in controlled environments to investigate the effect of climate on chemical defences and insect herbivory in pedunculate oak ( Quercus robur L.) throughout most of its geographic range in Europe, while controlling for physical defences. The concentration of lignin, flavonoids, and total phenolics increased significantly with temperature, whereas both field herbivory and weight of spongy moth ( Lymantria dispar L.) larvae were negatively influenced by temperature. Lignin concentration positively influenced the weight of spongy moth larvae whereas it had no effect on field herbivory. We found no evidence of strong positive relationships between insect herbivory and larvae growth with leaf defences. Our study underscores the complexity of plant–herbivore interactions along climatic gradients and highlights the need for further research to disentangle these intricate relationships.

Room for renewables: A GIS-based agrivoltaics site suitability analysis in urbanized landscapes - Thomas Reher; Cas Lavaert; Sam Ottoy; Johan A. Martens; Jos Van Orshoven; Jan Cappelle; Jan Diels; Bram Van de Poel (Agricultural Systems, 2025)

Current state of plant conservation translocations across Europe: motivations, challenges and outcomes - Sandrine Godefroid; Sam Lacquaye; Andreas Ensslin; Sarah Dalrymple; Thomas Abeli; Hannah Branwood; Inmaculada Ferrando Pardo; P. Pablo Ferrer Gallego; Elke Zippel; Luísa Gouveia; Carlos Alberto Lobo; Francisco Fernandes; et al. (Biodiversity and Conservation, 2025)

Counteracting uncertainty: exploring the impact of anxiety on updating predictions about environmental states - David Harris; Tom Arthur; Mark Wilson; Ben Le Gallais; Thomas Parsons; Ally Dill; Sam Vine (Biological Cybernetics, 2025)
Anxious emotional states disrupt decision-making and control of dexterous motor actions. Computational work has shown that anxiety-induced uncertainty alters the rate at which we learn about the environment, but the subsequent impact on the predictive beliefs that drive action control remains to be understood. In the present work we tested whether anxiety alters predictive (oculo)motor control mechanisms. Thirty participants completed an experimental task that consisted of manual interception of a projectile performed in virtual reality. Participants were subjected to conditions designed to induce states of high or low anxiety using performance incentives and social-evaluative pressure. We measured subsequent effects on physiological arousal, self-reported state anxiety, and eye movements. Under high pressure conditions we observed visual sampling of the task environment characterised by higher variability and entropy of position prior to release of the projectile, consistent with an active attempt to reduce uncertainty. Computational modelling of predictive beliefs, using gaze data as inputs to a partially observable Markov decision process model, indicated that trial-to-trial updating of predictive beliefs was reduced during anxiety, suggesting that updates to priors were constrained. Additionally, state anxiety was related to a less deterministic mapping of beliefs to actions. These results support the idea that organisms may attempt to counter anxiety-related uncertainty by moving towards more familiar and certain sensorimotor patterns.

Quantification and recovery prospects of critical metals and rare earth elements in Victorian brown coal fly ash: A promising secondary source for critical metal extraction - Bennet Sam Thomas; Sankar Bhattacharya (Hydrometallurgy, 2025)

Declines in greater bilby (Macrotis lagotis) geographic range and realised niche are best explained by the invasive red fox (Vulpes vulpes) - Hayley M. Geyle; Alys R. Young; Brett P. Murphy; Chris R. Dickman; Christine Schlesinger; Kelly M. Dixon; Harry Moore; Sarah Legge; Jennifer Silcock; Naomi Indigo; Martin Dziminski; Bruce Greatwich; et al. (Biological Conservation, 2025)

Developing Capacity for Transdisciplinary Studies of Changing Ocean Systems - Paul Renaud; Andrea Belgrano; Sam Dupont; Philip Boyd; Sinead Collins; Thomas Blenckner; Michael Drexler; Jason Hall-Spenser; Carol Robinson; Charlotte Weber; Cristian Vargas (Oceanography, 2025)
Addressing global challenges such as climate change requires large-scale collective actions, but such actions are hindered by the complexity and scale of the problem and the uncertainty in the long-term benefit of short-term actions (Jagers et al., 2019). In addition to climate change, socio-ecological systems face the cumulative pressures associated with resource needs, technology development, industrial expansion, and area conflicts. In marine systems, this has been called “the blue acceleration” (Jouffray et al., 2020) and is referred to as “socio-ecological pressures” in this paper. These socio-ecological pressures reduce our ability to reach the UN Sustainable Development Goals and meet the challenges of the UN Ocean Decade, and require integrating knowledge within a shared conceptual framework. For example, achieving sustainable growth must integrate ecological, socioeconomic, and governance perspectives on a larger scale by considering ecological impacts, ecosystem carrying capacities, economic trade-offs, social acceptability, and policy realities. This requires capacity development whereby actors unite to bridge disciplinary boundaries to meet challenges of complex systems.

Antarctic cushion star Odontaster validus larval performance is negatively impacted by long-term parental acclimation to elevated temperature - Miles Lamare; Maria Byrne; Bruno Danis; Dione Deaker; Matt Di Luccio; Sam Dupont; Shawna A. Foo; Tim Jowett; Sam Karelitz; Mary A. Sewell; Leighton J. Thomas; Antonio Agüera (Science of The Total Environment, 2024)

Processing of metal-free end-of-life tyres (EOLTs) to fuels and products: an experimental study with process simulation and economic analysis from an Australian perspective - Mahmud Arman Kibria; Bennet Sam Thomas; Mita Bhattacharya; Sankar Bhattacharya (Clean Technologies and Environmental Policy, 2024)
The aim of this experimental study, process simulation and economic analysis is to assess the applicability of pyrolysis technology for processing end-of-life tyres and to evaluate the economic viability of a 60 ton/day EOLT processing facility: a case-specific study within Australia. The experimental work and characterization of feedstock and products were carried out in-house. Capital costs for major equipment were collected from suppliers. The running cost of the processing facility is calculated on the basis of the current labour and utility costs. An economic model is developed based on the information generated from the experimental program and those obtained from suppliers. From the analysis, it is evident that the pyrolysis process for processing EOLT promises a significant upside in economic terms. A conservative conclusion of 20% light oil, ~ 65% furnace oil and 7% carbon black, generated as pyrolysis products, depicts a cash-flow positivity for a 60 tonne per day (TPD) plant that can be run using the generated fuel gas for under 4 years. This is in addition to the benefit of the zero landfill requirement. Apart from the base calculations, the sensitivity of six different scenarios is analysed by mainly changing the land cost and bank investment. Depending on the scenario, the calculated internal rate of return varies between 15 and 35%. While Australia generates significant quantities of EOLT, the techno-economic results confirm that pyrolysis technology for processing EOLT is a viable solution in Australia. However, a dedicated supply chain needs to exist to make pyrolysis plants an attractive investment at defined locations. Graphical abstract

Emissions from heavy-duty diesel, natural gas, and diesel-hybrid electric vehicles – Part 1. NOx, N2O and NH3 emissions - Hanwei Zhu; Chengguo Li; Cavan McCaffery; Sam Cao; Kent C. Johnson; Georgios Karavalakis; Thomas Durbin (Fuel, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Assessing the scale and ecological impact of derelict and discarded fishing gear across Thailand via the MARsCI citizen science protocol - Rahul Mehrotra; Coline Monchanin; Matthias Desmolles; Salisa Traipipitsiriwat; Dominic Chakrabongse; Amir Patel; Maythira Kasemsant; Sam Miyano Pitt; Tim McCabe; Trent McGrath; Claudia Marcellucci; Supatcha Japakang; et al. (Marine Pollution Bulletin, 2024)

Enabling factors and critical extensions for the algal-based bioplastics industry - Thomas Lee; Sam Wearne; Rachael Wakefield-Rann; Kate Scardifield (Journal of Cleaner Production, 2024)

Extraction and separation of rare earth elements from coal and coal fly ash: A review on fundamental understanding and on-going engineering advancements - Bennet Sam Thomas; Piet Dimitriadis; Chandan Kundu; Sai Sree Varsha Vuppaladadiyam; R.K. Singh Raman; Sankar Bhattacharya (Journal of Environmental Chemical Engineering, 2024)

Real-world particulate, GHG, and gaseous toxic emissions from heavy-duty diesel and natural gas vehicles - Zisimos Toumasatos; Hanwei Zhu; Thomas D. Durbin; Kent C. Johnson; Sam Cao; Georgios Karavalakis (Atmospheric Environment, 2024)

Decomposing drivers in avian insectivory: Large‐scale effects of climate, habitat and bird diversity - Laura Schillé; Elena Valdés‐Correcher; Frédéric Archaux; Flavius Bălăcenoiu; Mona Chor Bjørn; Michal Bogdziewicz; Thomas Boivin; Manuela Branco; Thomas Damestoy; Maarten de Groot; Jovan Dobrosavljević; Mihai‐Leonard Duduman; et al. (Journal of Biogeography, 2024)
Aim Climate is a major driver of large‐scale variability in biodiversity, as a likely result of more intense biotic interactions under warmer conditions. This idea fuelled decades of research on plant‐herbivore interactions, but much less is known about higher‐level trophic interactions. We addressed this research gap by characterizing both bird diversity and avian predation along a climatic gradient at the European scale. Location Europe. Taxon Insectivorous birds and pedunculate oaks. Methods We deployed plasticine caterpillars in 138 oak trees in 47 sites along a 19° latitudinal gradient in Europe to quantify bird insectivory through predation attempts. In addition, we used passive acoustic monitoring to (i) characterize the acoustic diversity of surrounding soundscapes; (ii) approximate bird abundance and activity through passive acoustic recordings; and (iii) infer both taxonomic and functional diversity of insectivorous birds from recordings. Results The functional diversity of insectivorous birds increased with warmer climates. Bird predation increased with forest cover and bird acoustic activity but decreased with mean annual temperature and functional richness of insectivorous birds. Contrary to our predictions, climatic clines in bird predation attempts were not directly mediated by changes in insectivorous bird diversity or acoustic activity, but climate and habitat still had independent effects on predation attempts. Main Conclusions Our study supports the hypothesis of an increase in the diversity of insectivorous birds towards warmer climates but refutes the idea that an increase in diversity would lead to more predation and advocates for better accounting for activity and abundance of insectivorous birds when studying the large‐scale variation in insect‐tree interactions.

Can e-waste recycling provide a solution to the scarcity of rare earth metals? An overview of e-waste recycling methods - Sai Sree Varsha Vuppaladadiyam; Bennet Sam Thomas; Chandan Kundu; Arun K. Vuppaladadiyam; Huabo Duan; Sankar Bhattacharya (Science of The Total Environment, 2024)

Damage to tropical forests caused by cyclones is driven by wind speed but mediated by topographical exposure and tree characteristics - Thomas Ibanez; David Bauman; Shin‐ichiro Aiba; Thomas Arsouze; Peter J. Bellingham; Chris Birkinshaw; Philippe Birnbaum; Timothy J. Curran; Saara J. DeWalt; John Dwyer; Thierry Fourcaud; Janet Franklin; et al. (Global Change Biology, 2024)
Each year, an average of 45 tropical cyclones affect coastal areas and potentially impact forests. The proportion of the most intense cyclones has increased over the past four decades and is predicted to continue to do so. Yet, it remains uncertain how topographical exposure and tree characteristics can mediate the damage caused by increasing wind speed. Here, we compiled empirical data on the damage caused by 11 cyclones occurring over the past 40 years, from 74 forest plots representing tropical regions worldwide, encompassing field data for 22,176 trees and 815 species. We reconstructed the wind structure of those tropical cyclones to estimate the maximum sustained wind speed (MSW) and wind direction at the studied plots. Then, we used a causal inference framework combined with Bayesian generalised linear mixed models to understand and quantify the causal effects of MSW, topographical exposure to wind (EXP), tree size (DBH) and species wood density ( ρ ) on the proportion of damaged trees at the community level, and on the probability of snapping or uprooting at the tree level. The probability of snapping or uprooting at the tree level and, hence, the proportion of damaged trees at the community level, increased with increasing MSW, and with increasing EXP accentuating the damaging effects of cyclones, in particular at higher wind speeds. Higher ρ decreased the probability of snapping and to a lesser extent of uprooting. Larger trees tended to have lower probabilities of snapping but increased probabilities of uprooting. Importantly, the effect of ρ decreasing the probabilities of snapping was more marked for smaller than larger trees and was further accentuated at higher MSW. Our work emphasises how local topography, tree size and species wood density together mediate cyclone damage to tropical forests, facilitating better predictions of the impacts of such disturbances in an increasingly windier world.

High resilience of Pacific Island forests to a category- 5 cyclone - Tamara Ticktin; Ashley McGuigan; Frazer Alo; Michael J. Balick; Andre Boraks; Chanel Sam; Thomas Doro; Presley Dovo; Thomas Ibanez; Alivereti Naikatini; Tom A. Ranker; Marika V. Tuiwawa; et al. (Science of The Total Environment, 2024)

The effect of anesthesia on hemodynamics and outcome of patients undergoing thrombectomy after acute ischemic stroke: a retrospective analysis - Sofie Ordies; Thomas De Brauwer; Tom De Beule; Sven Van Poucke; Kim Bekelaar; Ben Van Bylen; Dieter Mesotten; Stockx Luc; Ludovic Ernon; Sam Van Boxstael; Pascal Vanelderen (Acta Neurologica Belgica, 2024)

Effects of personal exposure to the oxidative potential of PM2.5 on oxidative stress biomarkers in pregnant women - Anouk Marsal; Jean-Jacques Sauvain; Aurélien Thomas; Sarah Lyon-Caen; Lucille Joanna S. Borlaza; Claire Philippat; Jean-Luc Jaffrezo; Anne Boudier; Sophie Darfeuil; Rhabira Elazzouzi; Johanna Lepeule; Ryan Chartier; et al. (Science of The Total Environment, 2024)

Assessing the spatio-temporal tropospheric ozone and drought impacts on leaf growth and grain yield of wheat across Europe through crop modeling and remote sensing data - Thuy Huu Nguyen; Giovanni Alessandro Cappelli; Lisa Emberson; Gonzalez Fernandez Ignacio; Anisoara Irimescu; Savian Francesco; Ginaldi Fabrizio; Nathan Booth; George Boldeanu; Victoria Bermejo; Sam Bland; Michael Frei; et al. (European Journal of Agronomy, 2024)

Microplastic accumulation in sewer sediments and its potential entering the environment via combined sewer overflows: a study case in Paris - Minh Trang Nguyen; Ngoc Nam Phuong; Mohamed Saad; Bruno Tassin; Thomas Gillet; Sabrina Guérin-Rechdaoui; Sam Azimi; Vincent Rocher; Johnny Gasperi; Rachid Dris (Environmental Science and Pollution Research, 2024)

On-road NOx and NH3 emissions measurements from in-use heavy-duty diesel and natural gas trucks in the South Coast air Basin of California - Hanwei Zhu; Tianyi Ma; Zisimos Toumasatos; Sam Cao; Georgios Karavalakis; Kent C. Johnson; Thomas Durbin (Atmospheric Environment, 2024)

The aggradation of alluvial fans in response to monsoon variability over the last 400 ka in the Hajar Mountains, south-east Arabia - Sam Woor; David S.G. Thomas; Julie A. Durcan; Sallie L. Burrough; Ash Parton (Quaternary Science Reviews, 2023)

Soluble TNFR1 has greater reproducibility than IL-6 for the assessment of chronic inflammation in older adults: the case for a new inflammatory marker in aging - Thomas Laskow; Jacqueline Langdon; Sam Sepehri; Marcela Davalos-Bichara; Ravi Varadhan; Jeremy Walston (GeroScience, 2023)

Engineering multicomponent tissue by spontaneous adhesion of myogenic and adipogenic microtissues cultured with customized scaffolds - N. Stephanie Kawecki; Sam C.P. Norris; Yixuan Xu; Yifan Wu; Ashton R. Davis; Ester Fridman; Kathleen K. Chen; Rachelle H. Crosbie; Andrea J. Garmyn; Song Li; Thomas G. Mason; Amy C. Rowat (Food Research International, 2023)

Identification and characterization of Phaseolus vulgaris endornavirus 1, 2 and 3 in common bean cultivars of East Africa - Thomas J. Brine; Sam Crawshaw; Alex M. Murphy; Adrienne E. Pate; John P. Carr; Francis O. Wamonje (Virus Genes, 2023)
Persistent viruses include members of the family Endornavirus that cause no apparent disease and are transmitted exclusively via seed or pollen. It is speculated that these RNA viruses may be mutualists that enhance plant resilience to biotic and abiotic stresses. Using reverse transcription coupled polymerase chain reactions, we investigated if common bean ( Phaseolus vulgaris L.) varieties popular in east Africa were hosts for Phaseolus vulgaris endornavirus (PvEV) 1, 2 or 3. Out of 26 bean varieties examined, four were infected with PvEV1, three were infected with both PvEV1 and PvEV2 and three had infections of all three (PvEV) 1, 2 and 3. Notably, this was the first identification of PvEV3 in common bean from Africa. Using high-throughput sequencing of two east African bean varieties (KK022 and KK072), we confirmed the presence of these viruses and generated their genomes. Intra- and inter-species sequence comparisons of these genomes with comparator sequences from GenBank revealed clear species demarcation. In addition, phylogenetic analyses based on sequences generated from the helicase domains showed that geographical distribution does not correlate to genetic relatedness or the occurrence of endornaviruses. These findings are an important first step towards future investigations to determine if these viruses engender positive effects in common bean, a vital crop in east Africa.

Evolution of functional group of lignocellulosic biomass and its delignified form during thermal conversion using synchrotron-based THz and laboratory-based in-situ DRIFT spectroscopy - Chandan Kundu; Saheli Biswas; Bennet Sam Thomas; Dominique Appadoo; Alex Duan; Sankar Bhattacharya (Fuel, 2023)

Clean heating: Reforming taxes and levies on heating fuels in Europe - Jan Rosenow; Sam Thomas; Duncan Gibb; Ruben Baetens; Andries De Brouwer; Jan Cornillie (Energy Policy, 2023)

Morphology and controls of the mountain-front fan systems of the Hajar Mountains, south-east Arabia - Sam Woor; David S.G. Thomas; Ash Parton; Anya Leenman (Earth-Science Reviews, 2023)

Transition from volcano-sagging to volcano-spreading - Eoghan P. Holohan; Sam Poppe; Audray Delcamp; Paul K. Byrne; Thomas R. Walter; Benjamin van Wyk de Vries; Matthieu Kervyn (Earth and Planetary Science Letters, 2023)

World Trade Center Site Exposure Duration Is Associated with Hippocampal and Cerebral White Matter Neuroinflammation - Chuan Huang; Minos Kritikos; Mario Serrano Sosa; Thomas Hagan; Alan Domkan; Jaymie Meliker; Alison C. Pellecchia; Stephanie Santiago-Michels; Melissa A. Carr; Roman Kotov; Megan Horton; Sam Gandy; et al. (Molecular Neurobiology, 2023)
Responders to the World Trade Center (WTC) attacks on 9/11/2001 inhaled toxic dust and experienced severe trauma for a prolonged period. Studies report that WTC site exposure duration is associated with peripheral inflammation and risk for developing early-onset dementia (EOD). Free Water Fraction (FWF) can serve as a biomarker for neuroinflammation by measuring in vivo movement of free water across neurons. The present case-controlled study aimed to examine associations between WTC site exposure duration as well as EOD status with increased hippocampal and cerebral neuroinflammation. Ninety-nine WTC responders (mean age of 56) were recruited between 2017 and 2019 ( N = 48 with EOD and 51 cognitively unimpaired). Participants were matched on age, sex, occupation, race, education, and post-traumatic stress disorder (PTSD) status. Participants underwent neuroimaging using diffusion tensor imaging protocols for FWF extraction. Region of interest (ROI) analysis and correlational tractography explored topographical distributions of FWF associations. Apolipoprotein-e4 allele ( APOE ε4) status was available for most responders ( N = 91). Hippocampal FWF was significantly associated with WTC site exposure duration ( r = 0.30, p = 0.003), as was cerebral white matter FWF ( r = 0.20, p = 0.044). ROI analysis and correlational tractography identified regions within the limbic, frontal, and temporal lobes. Hippocampal FWF and its association with WTC exposure duration were highest when the APOE ε4 allele was present ( r = 0.48, p = 0.039). Our findings demonstrate that prolonged WTC site exposure is associated with increased hippocampal and cerebral white matter neuroinflammation in WTC responders, possibly exacerbated by possession of the APOE ε4 allele.

Cognitive performance in a South African cohort of people with HIV and comorbid major depressive disorder - Anna J. Dreyer; Sam Nightingale; Lena S. Andersen; Jasper S. Lee; Hetta Gouse; Steven A. Safren; Conall O’Cleirigh; Kevin G. F. Thomas; John Joska (Journal of NeuroVirology, 2022)

Understanding the consequences of sea level rise: the ecological implications of losing intertidal habitat - Vera Rullens; Stephanie Mangan; Fabrice Stephenson; Dana E. Clark; Richard H. Bulmer; Anna Berthelsen; Josie Crawshaw; Rebecca V. Gladstone‐Gallagher; Sam Thomas; Joanne I. Ellis; Conrad A. Pilditch (New Zealand Journal of Marine and Freshwater Research, 2022)
Sea level rise (SLR) has been described as one of the greatest potential causes of ecosystem disruption, putting many coastal areas at risk of irreversible changes. However, the loss of intertidal areas from SLR and the associated ecological and social repercussions receive little attention. Within estuaries, extensive intertidal areas harbour a variety of habitats and communities and represent hotspots of ecosystem functions. Any changes to their distribution or extent are likely to have far reaching implications. Here we summarise the ecological consequences of a reduction in intertidal area from increasing SLR, and the implications for people, management and planning. To facilitate this discussion, changes in the occurrence and abundance of two ecologically and culturally important intertidal shellfish species ( Austrovenus stutchburyi and Macomona liliana ) were modelled under different SLR scenarios for Tauranga Harbour, Aotearoa New Zealand. We highlight how the squeezing of intertidal areas will likely alter the distribution and extent of key habitats and communities, and discuss the implications for coastal food webs, ecosystem functioning and service provision. Pre‐emptive planning and adaptive management are needed that incorporate ecological losses in risk assessments and focuses on pro‐active solutions to increase resilience to the effects of SLR.

The effect of edge serration on the performance of stone-tip projectiles: an experimental case study of the Maros Point from Holocene South Sulawesi - Anton Ferdianto; Suryatman; Fakhri; Budianto Hakim; Thomas Sutikna; Sam C. Lin (Archaeological and Anthropological Sciences, 2022)
Serrated stone points have been documented in a variety of archaeological settings worldwide. In Indonesia, serrated points known as Maros point began to appear during the mid-Holocene as part of the Toalean techno-complex in southern South Sulawesi. Researchers have speculated functional and cultural reason behind the emergence of these distinctive artefact as projectile points, an assumption that has yet to be verified by archaeological data. In particular, the edge serration has been suggested to allow for deeper penetration and/or act as barbs to prevent the easy withdrawal of the points from the target. In this study, we experimentally test these functional hypotheses regarding the effect of edge serration on stone arrowheads resembling Maros points when fired using different bow draw weights. We also investigate variation in breakage and impact fracture pattern between serrated and non-serrated points. Our result show that, compared to the non-serrated points, the serrated arrows not only deliver deeper penetrations, but also require less force to withdraw from the ballistic gel target. However, these relationships are complicated by the inclusion of skin and bone in the ballistic target. The findings demonstrate that the effect of serrated stone points on projectile performance depends on factors such as the projectile delivery system and prey type. Moreover, under identical firing settings, the serrated points develop more variable macrofracture patterns than the non-serrated points, likely owing the irregular edge morphologies. Taking these results together, we discuss the implications of our experimental study on the appearance of Maros points and the Toalean techno-complex in South Sulawesi during the mid-Holocene.

Can Stomach Content and Microbiomes of Tuna Provide Near Real-Time Detection of Ecosystem Composition in the Pacific Ocean? - Alejandro Trujillo-González; Teng Li; Joanne Potts; Simon Nicol; Valerie Allain; Sam C. Godwin; Elodie Vourey; Annie Portal; Brian Kumasi; Thomas Usu; Allen Rodrigo; Dianne Gleeson (Frontiers in Marine Science, 2022)
This preliminary study used DNA metabarcoding to test whether the stomach content and gut microbiome of tuna could be a viable near real-time monitoring tool for detecting composition and change in oceanic ecosystems. The gut content of skipjack ( Katsuwonus pelamis , n=55) and yellowfin tuna ( Thunnus albacares , n=46) captured in the Pacific Ocean during El Niño Southern Oscillation events (ENSO) between 2015-2017 were examined by high throughput sequencing and complemented by morphological assessments to identify fishes, crustaceans and cephalopods in the stomach content. Gut microbiome was examined solely by high throughput sequencing. Stomach content and gut microbiome were compared between tuna species, ENSO events and capture location using generalised linear models. The full model (tuna species, capture location and interaction with ENSO) best explained fish prey composition, while capture location and ENSO weakly explained the composition of crustaceans and cephalopods. Skipjack and yellowfin tuna captured near coastal areas (Longitude<170°W) showed a greater diversity of prey compared to fish captured in oceanic regions of the Pacific, while Thunnus albacares showed a much more diverse stomach content than K. pelamis (21 fish, eight cephalopods and six crustaceans). Fish captured during La Niña events showed higher prey diversity compared to fish captured during El Niño. Tuna species best explained differences in gut microbiome to the Phylum level, while no model explained gut microbiome differences to the Order or Family level. This preliminary study shows that capture location and ENSO events explained differences in stomach content of K. pelamis and T. albacares, while tuna species best explained gut microbiome assemblages to the Phylum level.

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

An Assessment of Economic Viability of the Ascension Island Tuna Longline Fishery Management: Implications for Marine Protected Area Planning and Future Fisheries Management - Angela Muench; Elena Mengo; Sam Weber; Diane Baum; Andrew James Richardson; Hannah Thomas; Paul Whomersley (Frontiers in Marine Science, 2022)
The designation of large scale marine protected areas (MPAs) has increased in recent years to address global issues such as biodiversity loss and the conservation of vulnerable marine habitats. While designing a large scale MPAs in the Exclusive Economic Zone (EEZ) of Ascension Island, the monitoring and enforcement costs were estimated for the two options under consideration: partial closure or full closure of the EEZ for the international commercial fleet. It was found that number of licenses to be sold to the international fleet to allow them access to the EEZ of Ascension Island would need to be increased to fund the monitoring and enforcement cost in case of a partial closure of the EEZ of Ascension Island. In this study, the future economic viability of the licensed big eye tuna fishery was addressed. The study explored economic drivers thought to be linked to license sales. It was shown that cost of licenses had not caused the observed decline in license sales but a shift in consumer demand toward lighter tuna species resulted in a decrease in Japanese imports for bigeye tuna ( Thunnus obesus ). This change in demand led to global changes in fishing effort and a drop in demand for licenses to fish within the Ascension Island EEZ. This study provided a valuable insight into the economic viability of the bigeye tuna fishery within the Ascension Island EEZ which informed the subsequent decision to close the bigeye tuna fishery as part of the designation of an Ascension Island highly protected large-scale MPA.

Immunomodulatory properties of characellide A on human peripheral blood mononuclear cells - Simone Marcella; Sam Afoullouss; Olivier P. Thomas; A. Louise Allcock; Paul V. Murphy; Stefania Loffredo (Inflammopharmacology, 2021)
Marine sponges and their associated microbiota are multicellular animals known to produce metabolites with interesting pharmacological properties playing a pivotal role against a plethora of pathologic disorders such as inflammation, cancer and infections. Characellide A and B belong to a novel class of glycolipopeptides isolated from the deep sea marine sponge Characella pachastrelloides . In this study, we have evaluated the effects of characellide A and B on cytokine and chemokine release from human peripheral blood mononuclear cells (PBMC). Characellide A induces a concentration- and time-dependent CXCL8, IL-6 and TNF-α release from PBMC. This production is mediated by the induction of gene transcription. Moreover, cytokine/chemokine release induced by characellide A from PBMC is CD1d-dependent because a CD1d antagonist, 1,2-bis(diphenylphosphino)ethane [DPPE]-polyethylene glycolmonomethylether [PEG], specifically inhibits characellide A-induced activation of PBMC. In conclusion, characellide A is a novel modulator of adaptative/innate immune responses. Further studies are needed to understand its potential pharmacological application.

Rates of cognitive impairment in a South African cohort of people with HIV: variation by definitional criteria and lack of association with neuroimaging biomarkers - Anna J. Dreyer; Sam Nightingale; Jodi M. Heaps-Woodruff; Michelle Henry; Hetta Gouse; Robert H. Paul; Kevin G. F. Thomas; John A. Joska (Journal of NeuroVirology, 2021)

Large potential for crop production adaptation depends on available future varieties - Florian Zabel; Christoph Müller; Joshua Elliott; Sara Minoli; Jonas Jägermeyr; Julia M. Schneider; James A. Franke; Elisabeth Moyer; Marie Dury; Louis Francois; Christian Folberth; Wenfeng Liu; et al. (Global Change Biology, 2021)
Climate change affects global agricultural production and threatens food security. Faster phenological development of crops due to climate warming is one of the main drivers for potential future yield reductions. To counter the effect of faster maturity, adapted varieties would require more heat units to regain the previous growing period length. In this study, we investigate the effects of variety adaptation on global caloric production under four different future climate change scenarios for maize, rice, soybean, and wheat. Thereby, we empirically identify areas that could require new varieties and areas where variety adaptation could be achieved by shifting existing varieties into new regions. The study uses an ensemble of seven global gridded crop models and five CMIP6 climate models. We found that 39% (SSP5‐8.5) of global cropland could require new crop varieties to avoid yield loss from climate change by the end of the century. At low levels of warming (SSP1‐2.6), 85% of currently cultivated land can draw from existing varieties to shift within an agro‐ecological zone for adaptation. The assumptions on available varieties for adaptation have major impacts on the effectiveness of variety adaptation, which could more than half in SSP5‐8.5. The results highlight that region‐specific breeding efforts are required to allow for a successful adaptation to climate change.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Search for top‐down and bottom‐up drivers of latitudinal trends in insect herbivory in oak trees in Europe - Elena Valdés‐Correcher; Xoaquín Moreira; Laurent Augusto; Luc Barbaro; Christophe Bouget; Olivier Bouriaud; Manuela Branco; Giada Centenaro; György Csóka; Thomas Damestoy; Jovan Dobrosavljević; Mihai‐Leonard Duduman; et al. (Global Ecology and Biogeography, 2021)
Aim The strength of species interactions is traditionally expected to increase toward the Equator. However, recent studies have reported opposite or inconsistent latitudinal trends in the bottom‐up (plant quality) and top‐down (natural enemies) forces driving herbivory. In addition, these forces have rarely been studied together thus limiting previous attempts to understand the effect of large‐scale climatic gradients on herbivory. Location Europe. Time period 2018–2019. Major taxa studied Quercus robur . Methods We simultaneously tested for latitudinal variation in plant–herbivore–natural enemy interactions. We further investigated the underlying climatic factors associated with variation in herbivory, leaf chemistry and attack rates in Quercus robur across its complete latitudinal range in Europe. We quantified insect leaf damage and the incidence of specialist herbivores as well as leaf chemistry and bird attack rates on dummy caterpillars on 261 oak trees. Results Climatic factors rather than latitude per se were the best predictors of the large‐scale (geographical) variation in the incidence of gall‐inducers and leaf‐miners as well as in leaf nutritional content. However, leaf damage, plant chemical defences (leaf phenolics) and bird attack rates were not influenced by climatic factors or latitude. The incidence of leaf‐miners increased with increasing concentrations of hydrolysable tannins, whereas the incidence of gall‐inducers increased with increasing leaf soluble sugar concentration and decreased with increasing leaf C : N ratios and lignins. However, leaf traits and bird attack rates did not vary with leaf damage. Main conclusions These findings help to refine our understanding of the bottom‐up and top‐down mechanisms driving geographical variation in plant–herbivore interactions, and indicate the need for further examination of the drivers of herbivory on trees.

Pantropical variability in tree crown allometry - Grace Jopaul Loubota Panzou; Adeline Fayolle; Tommaso Jucker; Oliver L. Phillips; Stephanie Bohlman; Lindsay F. Banin; Simon L. Lewis; Kofi Affum‐Baffoe; Luciana F. Alves; Cécile Antin; Eric Arets; Luzmila Arroyo; et al. (Global Ecology and Biogeography, 2021)
Aim Tree crowns determine light interception, carbon and water exchange. Thus, understanding the factors causing tree crown allometry to vary at the tree and stand level matters greatly for the development of future vegetation modelling and for the calibration of remote sensing products. Nevertheless, we know little about large‐scale variation and determinants in tropical tree crown allometry. In this study, we explored the continental variation in scaling exponents of site‐specific crown allometry and assessed their relationships with environmental and stand‐level variables in the tropics. Location Global tropics. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 87,737 trees distributed among 245 forest and savanna sites across the tropics, we fitted site‐specific allometric relationships between crown dimensions (crown depth, diameter and volume) and stem diameter using power‐law models. Stand‐level and environmental drivers of crown allometric relationships were assessed at pantropical and continental scales. Results The scaling exponents of allometric relationships between stem diameter and crown dimensions were higher in savannas than in forests. We identified that continental crown models were better than pantropical crown models and that continental differences in crown allometric relationships were driven by both stand‐level (wood density) and environmental (precipitation, cation exchange capacity and soil texture) variables for both tropical biomes. For a given diameter, forest trees from Asia and savanna trees from Australia had smaller crown dimensions than trees in Africa and America, with crown volumes for some Asian forest trees being smaller than those of trees in African forests. Main conclusions Our results provide new insight into geographical variability, with large continental differences in tropical tree crown allometry that were driven by stand‐level and environmental variables. They have implications for the assessment of ecosystem function and for the monitoring of woody biomass by remote sensing techniques in the global tropics.

Upper and lower treeline biogeographic patterns in semi‐arid pinyon‐juniper woodlands - Matteo Garbarino; Francesco Malandra; Thomas Dilts; Sam Flake; Luigi Montalto; Susanna Spinsante; Peter J. Weisberg (Journal of Biogeography, 2020)
Aim Upper and lower treelines are particularly exposed to a changing climate. It has been hypothesized that upper treelines are constrained by growing season temperature, whereas lower tree lines are water limited. We expect different causal mechanisms of upper versus lower tree line formation to generate distinct patterns of spatial heterogeneity. Here, we compare dynamics, spatial patterns and shape complexity of upper and lower tree lines of semi‐arid pinyon‐juniper woodlands. Location Toiyabe Range of the Nevada Great Basin (western US). Taxon Pinus monophylla Torr. & Frém. and Juniperus osteosperma (Torr.) Methods Within 20 sample plots (10 along the upper and 10 along the lower tree line), we mapped tree canopies through photointerpretation of high‐resolution imagery. We performed point pattern analyses to compare the spatial arrangement of trees and used LANDSAT 30‐year time series and NDVI to understand the vegetation dynamics of these ecotones. We adopted the surface roughness method to measure tree line shape complexity. Results Lower tree lines were denser and showed a stronger trend of increasing NDVI change over the 1984–2015 period. Trees at the lower tree line were more strongly aggregated than at the upper tree line at spatial scales ranging from 15 to 65 meters. Shape complexity was higher at upper tree lines, expressed by a higher mean surface roughness; however, the spatial structures of upper and lower tree lines were similar. Main conclusions Upper tree line expansion of pinyon‐juniper woodlands in the study area has been limited and highly variable, but lower tree line downslope expansion into adjacent shrub steppe vegetation was evident. The expected difference between energy‐ and water‐limited tree lines did not manifest in the observed spatial structures. Differences in tree line shape complexity were not significant, although lower tree lines exhibited less complex shapes, likely because they have been more strongly influenced by anthropogenic factors.

Variability of Skin Pharmacokinetic Data: Insights from a Topical Bioequivalence Study Using Dermal Open Flow Microperfusion - Manfred Bodenlenz; Thomas Augustin; Thomas Birngruber; Katrin I. Tiffner; Beate Boulgaropoulos; Simon Schwingenschuh; Sam G. Raney; Elena Rantou; Frank Sinner (Pharmaceutical Research, 2020)
Purpose Dermal open flow microperfusion (dOFM) has previously demonstrated its utility to assess the bioequivalence (BE) of topical drug products in a clinical study. We aimed to characterize the sources of variability in the dermal pharmacokinetic data from that study. Methods Exploratory statistical analyses were performed with multivariate data from a clinical dOFM-study in 20 healthy adults evaluating the BE, or lack thereof, of Austrian test (T) and U.S. reference (R) acyclovir cream, 5% products. Results The overall variability of logAUC values (CV: 39% for R and 45% for T) was dominated by inter-subject variability (R: 82%, T: 91%) which correlated best with the subject’s skin conductance. Intra-subject variability was 18% (R) and 9% (T) of the overall variability; skin treatment sites or methodological factors did not significantly contribute to that variability. Conclusions Inter-subject variability was the major component of overall variability for acyclovir, and treatment site location did not significantly influence intra-subject variability. These results support a dOFM BE study design with T and R products assessed simultaneously on the same subject, where T and R treatment sites do not necessarily need to be next to each other. Localized variation in skin microstructure may be primarily responsible for intra-subject variability.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Population collapse and retreat to fire refugia of the Tasmanian endemic conifer Athrotaxis selaginoides following the transition from Aboriginal to European fire management - Andrés Holz; Sam W. Wood; Carly Ward; Thomas T. Veblen; David M. J. S. Bowman (Global Change Biology, 2020)
Untangling the nuanced relationships between landscape, fire disturbance, human agency, and climate is key to understanding rapid population declines of fire‐sensitive plant species. Using multiple lines of evidence across temporal and spatial scales (vegetation survey, stand structure analysis, dendrochronology, and fire history reconstruction), we document landscape‐scale population collapse of the long‐lived, endemic Tasmanian conifer Athrotaxis selaginoides in remote montane catchments in southern Tasmania. We contextualized the findings of this field‐based study with a Tasmanian‐wide geospatial analysis of fire‐killed and unburned populations of the species. Population declines followed European colonization commencing in 1802 ad that disrupted Aboriginal landscape burning. Prior to European colonization, fire events were infrequent but frequency sharply increased afterwards. Dendrochronological analysis revealed that reconstructed fire years were associated with abnormally warm/dry conditions, with below‐average streamflow, and were strongly teleconnected to the Southern Annular Mode. The multiple fires that followed European colonization caused near total mortality of A. selaginoides and resulted in pronounced floristic, structural vegetation, and fuel load changes. Burned stands have very few regenerating A. selaginoides juveniles yet tree‐establishment reconstruction of fire‐killed adults exhibited persistent recruitment in the period prior to European colonization. Collectively, our findings indicate that this fire‐sensitive Gondwanan conifer was able to persist with burning by Aboriginal Tasmanians, despite episodic widespread forest fires. By contrast, European burning led to the restriction of A. selaginoides to prime topographic fire refugia. Increasingly, frequent fires caused by regional dry and warming trends and increased ignitions by humans and lightning are breaching fire refugia; hence, the survival Tasmanian Gondwanan species demands sustained and targeted fire management.

Mapping of the stem rust resistance gene Pg13 in cultivated oat - Aida Z. Kebede; Belayneh Admassu-Yimer; Wubishet A. Bekele; Tyler Gordon; J. Michael Bonman; Ebrahiem Babiker; Yue Jin; Sam Gale; Charlene P. Wight; Nicholas A. Tinker; Jim G. Menzies; Aaron D. Beattie; et al. (Theoretical and Applied Genetics, 2020)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

Sex‐specific changes in the aphid DNA methylation landscape - Thomas C. Mathers; Sam T. Mugford; Lawrence Percival‐Alwyn; Yazhou Chen; Gemy Kaithakottil; David Swarbreck; Saskia A. Hogenhout; Cock van Oosterhout (Molecular Ecology, 2019)
Aphids present an ideal system to study epigenetics as they can produce diverse, but genetically identical, morphs in response to environmental stimuli. Here, using whole genome bisulphite sequencing and transcriptome sequencing of the green peach aphid ( Myzus persicae ), we present the first detailed analysis of cytosine methylation in an aphid and investigate differences in the methylation and transcriptional landscapes of male and asexual female morphs. We found that methylation primarily occurs in a CG dinucleotide (CpG) context and that exons are highly enriched for methylated CpGs, particularly at the 3′ end of genes. Methylation is positively associated with gene expression, and methylated genes are more stably expressed than unmethylated genes. Male and asexual female morphs have distinct methylation profiles. Strikingly, these profiles are divergent between the sex chromosome and the autosomes; autosomal genes are hypomethylated in males compared to asexual females, whereas genes belonging to the sex chromosome, which is haploid in males, are hypermethylated. Overall, we found correlated changes in methylation and gene expression between males and asexual females, and this correlation was particularly strong for genes located on the sex chromosome. Our results suggest that differential methylation of sex‐biased genes plays a role in aphid sexual differentiation.

The diversity of population responses to environmental change - Fernando Colchero; Owen R. Jones; Dalia A. Conde; David Hodgson; Felix Zajitschek; Benedikt R. Schmidt; Aurelio F. Malo; Susan C. Alberts; Peter H. Becker; Sandra Bouwhuis; Anne M. Bronikowski; Kristel M. De Vleeschouwer; et al. (Ecology Letters, 2019)
The current extinction and climate change crises pressure us to predict population dynamics with ever‐greater accuracy. Although predictions rest on the well‐advanced theory of age‐structured populations, two key issues remain poorly explored. Specifically, how the age‐dependency in demographic rates and the year‐to‐year interactions between survival and fecundity affect stochastic population growth rates. We use inference, simulations and mathematical derivations to explore how environmental perturbations determine population growth rates for populations with different age‐specific demographic rates and when ages are reduced to stages. We find that stage‐ vs. age‐based models can produce markedly divergent stochastic population growth rates. The differences are most pronounced when there are survival‐fecundity‐trade‐offs, which reduce the variance in the population growth rate. Finally, the expected value and variance of the stochastic growth rates of populations with different age‐specific demographic rates can diverge to the extent that, while some populations may thrive, others will inevitably go extinct.

Cardiovascular pharmacology of K2P17.1 (TASK-4, TALK-2) two-pore-domain K+ channels - Ingo Staudacher; Claudius Illg; Sam Chai; Isabelle Deschenes; Sebastian Seehausen; Dominik Gramlich; Mara Elena Müller; Teresa Wieder; Ann-Kathrin Rahm; Christina Mayer; Patrick A. Schweizer; Hugo A. Katus; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

The accessibility and utilization of genetic testing for inherited heart rhythm disorders: a Canadian cross-sectional survey study - Thomas M. Roston; Laura Dewar; Sonia Franciosi; Julie Hathaway; Kirsten Bartels; Taylor Cunningham; Karen A. Gibbs; Sam Sheps; Zachary W. M. Laksman; Shubhayan Sanatani; Andrew D. Krahn (Journal of Community Genetics, 2018)

Adaptation of global land use and management intensity to changes in climate and atmospheric carbon dioxide - Peter Alexander; Sam Rabin; Peter Anthoni; Roslyn Henry; Thomas A. M. Pugh; Mark D. A. Rounsevell; Almut Arneth (Global Change Biology, 2018)
Land use contributes to environmental change, but is also influenced by such changes. Climate and atmospheric carbon dioxide ( CO 2 ) levels’ changes alter agricultural crop productivity, plant water requirements and irrigation water availability. The global food system needs to respond and adapt to these changes, for example, by altering agricultural practices, including the crop types or intensity of management, or shifting cultivated areas within and between countries. As impacts and associated adaptation responses are spatially specific, understanding the land use adaptation to environmental changes requires crop productivity representations that capture spatial variations. The impact of variation in management practices, including fertiliser and irrigation rates, also needs to be considered. To date, models of global land use have selected agricultural expansion or intensification levels using relatively aggregate spatial representations, typically at a regional level, that are not able to characterise the details of these spatially differentiated responses. Here, we show results from a novel global modelling approach using more detailed biophysically derived yield responses to inputs with greater spatial specificity than previously possible. The approach couples a dynamic global vegetative model ( LPJ ‐ GUESS ) with a new land use and food system model ( PLUM v2), with results benchmarked against historical land use change from 1970. Land use outcomes to 2100 were explored, suggesting that increased intensity of climate forcing reduces the inputs required for food production, due to the fertilisation and enhanced water use efficiency effects of elevated atmospheric CO 2 concentrations, but requiring substantial shifts in the global and local patterns of production. The results suggest that adaptation in the global agriculture and food system has substantial capacity to diminish the negative impacts and gain greater benefits from positive outcomes of climate change. Consequently, agricultural expansion and intensification may be lower than found in previous studies where spatial details and processes consideration were more constrained.

Development of an In Vitro PIV Setup for Preliminary Investigation of the Effects of Aortic Compliance on Flow Patterns and Hemodynamics - Martin Büsen; Christian Arenz; Michael Neidlin; Sam Liao; Thomas Schmitz-Rode; Ulrich Steinseifer; Simon J. Sonntag (Cardiovascular Engineering and Technology, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

The Tritiated Water Skin Barrier Integrity Test: Considerations for Acceptance Criteria with and Without 14C-Octanol - Paul A. Lehman; Kacie Beatch; Sam G. Raney; Thomas J. Franz (Pharmaceutical Research, 2017)

Observations of a New Zealand dolphin ( Cephalorhynchus hectori ) breathing via its mouth - Stephen M. Dawson; R. Ewan Fordyce; Sam H. Ridgway; Thomas E. Brough; Elisabeth Slooten (Marine Mammal Science, 2017)

Conservation gone to the dogs: when canids rule the beach in small coastal reserves - Thomas A. Schlacher; Michael A. Weston; David Lynn; David S. Schoeman; Chantal M. Huijbers; Andrew D. Olds; Sam Masters; Rod M. Connolly (Biodiversity and Conservation, 2015)

Effects of high‐severity fire drove the population collapse of the subalpine Tasmanian endemic conifer Athrotaxis cupressoides - Andrés Holz; Sam W. Wood; Thomas T. Veblen; David M.J.S. Bowman (Global Change Biology, 2015)
Athrotaxis cupressoides is a slow‐growing and long‐lived conifer that occurs in the subalpine temperate forests of Tasmania, a continental island to the south of Australia. In 1960–1961, human‐ignited wildfires occurred during an extremely dry summer that killed many A. cupressoides stands on the high plateau in the center of Tasmania. That fire year, coupled with subsequent regeneration failure, caused a loss of ca. 10% of the geographic extent of this endemic Tasmanian forest type. To provide historical context for these large‐scale fire events, we (i) collected dendroecological, floristic, and structural data, (ii) documented the postfire survival and regeneration of A. cupressoides and co‐occurring understory species, and (iii) assessed postfire understory plant community composition and flammability. We found that fire frequency did not vary following the arrival of European settlers, and that A. cupressoides populations were able to persist under a regime of low‐to‐mid severity fires prior to the 1960 fires. Our data indicate that the 1960 fires were (i) of greater severity than previous fires, (ii) herbivory by native marsupials may limit seedling survival in both burned and unburned A. cupressoides stands, and (iii) the loss of A. cupressoides populations is largely irreversible given the relatively high fuel loads of postfire vegetation communities that are dominated by resprouting shrubs. We suggest that the feedback between regeneration failure and increased flammability will be further exacerbated by a warmer and drier climate causing A. cupressoides to contract to the most fire‐proof landscape settings.

Thermal sensitivity to warmth during rest and exercise: a sex comparison - Nicola Gerrett; Yacine Ouzzahra; Samantha Coleby; Sam Hobbs; Bernard Redortier; Thomas Voelcker; George Havenith (European Journal of Applied Physiology, 2014)

Ionospheric threat simulation for GNSS using the Spirent hardware signal simulator - Thomas Dautermann; Matteo Sgammini; Sam Pullen (GPS Solutions, 2014)

Mammalian toxicology and human exposures to the flame retardant 2,2′,6,6′-tetrabromo-4,4′-isopropylidenediphenol (TBBPA): implications for risk assessment - Thomas Colnot; Sam Kacew; Wolfgang Dekant (Archives of Toxicology, 2013)

Potential for evolutionary responses to climate change – evidence from tree populations - Florian J. Alberto; Sally N. Aitken; Ricardo Alía; Santiago C. González‐Martínez; Heikki Hänninen; Antoine Kremer; François Lefèvre; Thomas Lenormand; Sam Yeaman; Ross Whetten; Outi Savolainen (Global Change Biology, 2013)
Evolutionary responses are required for tree populations to be able to track climate change. Results of 250 years of common garden experiments show that most forest trees have evolved local adaptation, as evidenced by the adaptive differentiation of populations in quantitative traits, reflecting environmental conditions of population origins. On the basis of the patterns of quantitative variation for 19 adaptation‐related traits studied in 59 tree species (mostly temperate and boreal species from the Northern hemisphere), we found that genetic differentiation between populations and clinal variation along environmental gradients were very common (respectively, 90% and 78% of cases). Thus, responding to climate change will likely require that the quantitative traits of populations again match their environments. We examine what kind of information is needed for evaluating the potential to respond, and what information is already available. We review the genetic models related to selection responses, and what is known currently about the genetic basis of the traits. We address special problems to be found at the range margins, and highlight the need for more modeling to understand specific issues at southern and northern margins. We need new common garden experiments for less known species. For extensively studied species, new experiments are needed outside the current ranges. Improving genomic information will allow better prediction of responses. Competitive and other interactions within species and interactions between species deserve more consideration. Despite the long generation times, the strong background in quantitative genetics and growing genomic resources make forest trees useful species for climate change research. The greatest adaptive response is expected when populations are large, have high genetic variability, selection is strong, and there is ecological opportunity for establishment of better adapted genotypes.

Local Participation in Natural Resource Monitoring: a Characterization of Approaches - FINN DANIELSEN; NEIL D. BURGESS; ANDREW BALMFORD; PAUL F. DONALD; MIKKEL FUNDER; JULIA P. G. JONES; PHILIP ALVIOLA; DANILO S. BALETE; TOM BLOMLEY; JUSTIN BRASHARES; BRIAN CHILD; MARTIN ENGHOFF; et al. (Conservation Biology, 2009)
The monitoring of trends in the status of species or habitats is routine in developed countries, where it is funded by the state or large nongovernmental organizations and often involves large numbers of skilled amateur volunteers. Far less monitoring of natural resources takes place in developing countries, where state agencies have small budgets, there are fewer skilled professionals or amateurs, and socioeconomic conditions prevent development of a culture of volunteerism. The resulting lack of knowledge about trends in species and habitats presents a serious challenge for detecting, understanding, and reversing declines in natural resource values. International environmental agreements require signatories undertake systematic monitoring of their natural resources, but no system exists to guide the development and expansion of monitoring schemes. To help develop such a protocol, we suggest a typology of monitoring categories, defined by their degree of local participation, ranging from no local involvement with monitoring undertaken by professional researchers to an entirely local effort with monitoring undertaken by local people. We assessed the strengths and weaknesses of each monitoring category and the potential of each to be sustainable in developed or developing countries. Locally based monitoring is particularly relevant in developing countries, where it can lead to rapid decisions to solve the key threats affecting natural resources, can empower local communities to better manage their resources, and can refine sustainable‐use strategies to improve local livelihoods. Nevertheless, we recognize that the accuracy and precision of the monitoring undertaken by local communities in different situations needs further study and field protocols need to be further developed to get the best from the unrealized potential of this approach. A challenge to conservation biologists is to identify and establish the monitoring system most relevant to a particular situation and to develop methods to integrate outputs from across the spectrum of monitoring schemes to produce wider indices of natural resources that capture the strengths of each.

Evolution of pathogens in a man‐made world - CAMILLE LEBARBENCHON; SAM P. BROWN; ROBERT POULIN; MICHEL GAUTHIER‐CLERC; FRÉDÉRIC THOMAS (Molecular Ecology, 2008)
Human activities have resulted in substantial, large‐scale environmental modifications, especially in the past century. Ecologists and evolutionary biologists are increasingly coming to realize that parasites and pathogens, like free‐living organisms, evolve as the consequence of these anthropogenic changes. Although this area now commands the attention of a variety of researchers, a broad predictive framework is lacking, mainly because the links between human activities, the environment and parasite evolution are complex. From empirical and theoretical examples chosen in the literature, we give an overview of the ways in which humans can directly or indirectly influence the evolution of different traits in parasites ( e.g. specificity, virulence, polymorphism). We discuss the role of direct and indirect factors as diverse as habitat fragmentation, pollution, biodiversity loss, climate change, introduction of species, use of vaccines and antibiotics, ageing of the population, etc. We also present challenging questions for further research. Understanding the links between anthropogenic changes and parasite evolution needs to become a cornerstone of public health planning, economic development and conservation biology.

Efficacy of Vegetated Buffers in Preventing Transport of Fecal Coliform Bacteria from Pasturelands - Timothy J. Sullivan; James A. Moore; David R. Thomas; Eric Mallery; Kai U. Snyder; Mark Wustenberg; Judith Wustenberg; Sam D. Mackey; Deian L. Moore (Environmental Management, 2007)

Vehicles versus conservation of invertebrates on sandy beaches: mortalities inflicted by off‐road vehicles on ghost crabs - Thomas A. Schlacher; Luke Thompson; Sam Price (Marine Ecology, 2007)
Sandy beaches face increasing anthropogenic pressures, with vehicle traffic being ecologically highly harmful. Ghost crabs (Fam. Ocypodidae) are conspicuous on many beaches, and they have been used as a bio‐monitoring tool to measure the ecological responses to human disturbance. However, the mechanisms causing declines in crab numbers are unknown, yet conservation must target the actual impact mechanisms. Therefore, we quantified the magnitude and mechanisms of off‐road vehicle (ORV) impacts on ghost crabs, addressing three key questions: (i) Does abundance of ghost crabs respond to traffic intensity?; (ii) Can burrows protect crabs from vehicles? and (iii) Can mortalities caused by vehicles contribute to population declines? ORV‐impacts were measured on North Stradbroke Island (Australia) for Ocypode cordimanus and Ocypode ceratophthalma . Crab densities were significantly lower in areas subjected to heavy beach traffic, suggesting direct crushing by vehicles. Burrows only partially protect crabs against cars: all individuals buried shallow (5 cm) are killed by 10 vehicle passes. Mortality declines with depth of burrows, but remains considerable (10–30% killed) at 20 cm and only those crabs buried at least 30 cm are not killed by ORVs: these ‘deep‐living’ crabs represent about half of the population. After crabs emerge at dusk they are killed in large numbers on the beach surface. A single vehicle can crush up to 0.75% of the intertidal population. While conservation measures should primarily regulate night traffic, our results also emphasise that the fossorial life habits of sandy beach animals cannot off‐set the impacts caused by ORVs.

Insect Pheromones and Precursors in Female African Elephant Urine - Thomas E. Goodwin; Mindy S. Eggert; Sam J. House; Margaret E. Weddell; Bruce A. Schulte; L. E. L. Rasmussen (Journal of Chemical Ecology, 2006)

Chromatin dynamics and the evolution of alternate promoter states - Gordon L. Hager; Cem Elbi; Thomas A. Johnson; Ty Voss; Akhilesh K. Nagaich; R. Louis Schiltz; Yi Qiu; Sam John (Chromosome Research, 2006)

Fever and phenotype: transgenerational effect of disease on desert locust phase state - Sam L. Elliot; Simon Blanford; Charlotte M. Horton; Matthew B. Thomas (Ecology Letters, 2003)
Natural enemy attack can cause transgenerational shifts in phenotype such that offspring are less vulnerable to future attack. Desert locusts ( Schistocerca gregaria ) show density‐dependent variation in their resistance to pathogens, such that they are less vulnerable to pathogens when in the high‐density gregarious phase state (when they would probably be more exposed to pathogens) than when in the solitarious phase state. We therefore hypothesized that infected gregarious parents would maintain this phenotype in their offspring. We infected gregarious desert locust nymphs with the fungal pathogen Metarhizium anisopliae var. acridum , and allowed them to survive to reproduction by means of behavioural fever. The phase state of the locust offspring was assessed by their colouration and behavioural assays. Contrary to our hypothesis, we found an increase in solitarization in the infected population (14.6% solitarious offspring from infected parents, vs.